Methaemalbumin: a diagnostic surrogate for methaemoglobinaemia and treatment with red cell exchange in a patient with thalassaemia. Issue 3 (7th March 2023) - Prus-Czarnecka, Zofia; Fuenzy, Anna Issac; Noga, Tom; Lau, Vincent Issac
Abstract : A man in his 30s with alpha thalassaemia (four-alpha globin gene deletion) presented with 1 week of shortness of breath and 1 month of general malaise. Pulse oximetry monitoring revealed low peripheral oxygen saturation of approximately 80% despite maximal high-flow nasal cannula oxygen (fractional inspired oxygen 1.0–60 L/min flow). Arterial blood gas samples were chocolate brown in colour, with a low arterial partial pressure of oxygen of 197 mm Hg. This large oxygen saturation gap raised suspicion for methaemoglobinaemia. However, the patient's co-oximetry results were suppressed by the blood gas analyser and delayed a definitive diagnosis. A methaemalbumin screen was sent instead, which was positive at 65 mg/L (reference interval: <3 mg/L). Treatment with methylene blue was initiated but did not result in complete resolution of cyanosis. This patient had been red cell exchange dependent since childhood for thalassaemia. Therefore, an urgent red cell exchange was initiated overnight, leading to an improvement in symptoms and interpretability of co-oximetry results. This resulted in rapid improvement without residual sequelae or complications. We conclude that a methaemalbumin screen can be used as a surrogate test for prompt confirmation of diagnosis in lieu of co-oximetry in cases of severe methaemoglobinaemia or in cases with underlying haemoglobinopathy. Red cell exchange can allow prompt methaemoglobinaemia reversal, especially if methylene blue is only partially effective.